1998
DOI: 10.1046/j.1365-2362.1998.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants inhibit the in vitro production of inflammatory cytokines in Crohn's disease and ulcerative colitis

Abstract: Our results suggest that the studied antioxidants, or related compounds, may be of interest in inflammatory bowel disease treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…Release of free radicals may increase intestinal mucosal damage and inflammation in Crohn's disease (Simmonds & Rampton, 1993;Grisham, 1994) and reduce bone mass through increased bone resorption and decreased bone formation (Parhami, 2003). Dietary supplementation with antioxidants decreases oxidative stress (Aghdassi et al 2003) and inhibits production of inflammatory mediators by PBMC (Reimund et al 1998) in Crohn's disease. Reduced availability of vitamin C and other antioxidant micronutrients, which may be noted in Crohn's disease (Kuroki et al 1993;Ringstad et al 1993;Buffinton & Doe, 1995), are associated with bone loss in post-menopausal women (Kaptoge et al 2003;Maggio et al 2003), but whether antioxidant supplementation has an effect on bone turnover is uncertain.…”
mentioning
confidence: 99%
“…Release of free radicals may increase intestinal mucosal damage and inflammation in Crohn's disease (Simmonds & Rampton, 1993;Grisham, 1994) and reduce bone mass through increased bone resorption and decreased bone formation (Parhami, 2003). Dietary supplementation with antioxidants decreases oxidative stress (Aghdassi et al 2003) and inhibits production of inflammatory mediators by PBMC (Reimund et al 1998) in Crohn's disease. Reduced availability of vitamin C and other antioxidant micronutrients, which may be noted in Crohn's disease (Kuroki et al 1993;Ringstad et al 1993;Buffinton & Doe, 1995), are associated with bone loss in post-menopausal women (Kaptoge et al 2003;Maggio et al 2003), but whether antioxidant supplementation has an effect on bone turnover is uncertain.…”
mentioning
confidence: 99%
“…Furthermore, this process is significantly enhanced and maintained by the presence of ascorbate, an endogenous antioxidant present in the brain at concentrations that rise to the millimolar range [39] and which may be regenerated by the action of dehydroascorbate dehydrogenase. However, THP itself does not cause lipid peroxidation and is even able to reduce it when induced by the presence of ascorbate and iron, which could explain the apparent antioxidant properties as reported by some authors [24,25]. On the contrary, THP is able to promote protein oxidation, a process that involves both an increase in the protein carbonyl content and a reduction in the protein free thiol content, which is exacerbated by the presence of ascorbate.…”
Section: Discussionmentioning
confidence: 84%
“…This is the mechanism used to explain the neurotoxicity of 6-hydroxydopamine (6-OHDA), a wellknown catecholaminergic neurotoxin widely used to create experimental models of Parkinson's disease. However, the presence of two catechol moieties in the chemical structure of THP has also been used to attribute antioxidant properties to this compound [24,25]. Furthermore, more recently it has been reported that the antioxidant activity of some phytochemicals and estrogens is directly related to the existence of a catechol group in the molecule [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant regulation of cytokines or their selective receptors may therefore contribute to the exacerbation of disease condition. Indeed, such dysregulation has been implicated in a number of human diseases, including sepsis syndrome (Beutler and Cerami, 1986), psoriasis (Elder et al, 1989), autosomal recessive disorders associated with premature aging (Bauer et al, 1986), adult respiratory distress syndrome (Bunnell and Pacht, 1993), idiopathic pulmonary fibrosis (Cantin et al, 1989), Crohn's disease and ulcerative colitis (Reimund et al, 1998), allergic bronchopulmonary aspergillosis (Wark and Gibson, 2001), bronchopulmonary dysplasia (Saugstad, 1997), cystic fibrosis (Doring, 1996;Zeiher and Hornick, 1996), and rheumatoid arthritis (Feldmann and Maini, 2001).…”
Section: Discussionmentioning
confidence: 99%